2015
DOI: 10.1111/jar.12231
|View full text |Cite
|
Sign up to set email alerts
|

Could Ethical Tensions in Oral Healthcare Management Revealed by Adults with Intellectual Disabilities and Caregivers Explain Unmet Oral Health Needs? Participatory Research with Focus Groups

Abstract: These discrepancies could partly explain multiple attempts to find the 'right' dentist or the fact that care was abandoned, and could at least contribute to oral health needs being unmet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(27 citation statements)
references
References 29 publications
0
27
0
Order By: Relevance
“…Poor attitudes held by both healthcare professionals and non-health professionals, across both primary and acute healthcare provider settings, is a recurring theme in the review’s identified studies. 22 , 31 33 A warm, friendly, and caring attitude from healthcare providers enables service users to access healthcare facilities and discuss sensitive health concerns. 22 , 34 37 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Poor attitudes held by both healthcare professionals and non-health professionals, across both primary and acute healthcare provider settings, is a recurring theme in the review’s identified studies. 22 , 31 33 A warm, friendly, and caring attitude from healthcare providers enables service users to access healthcare facilities and discuss sensitive health concerns. 22 , 34 37 …”
Section: Resultsmentioning
confidence: 99%
“…Fear and embarrassment is a barrier to accessing health care for individuals with intellectual disabilities and/or autism. 57 59 These include fears of being judged over lifestyle choices, of blood tests and vaccinations, 38 of medical instruments, 31 and fears associated with a lack of understanding about screening procedures. 59 Physical examinations can also be a source of embarrassment and/or discomfort for individuals with intellectual disabilities.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, discussion of the difficulties in these therapies should be introduced with attention and tact so as not to strengthen a feeling of inequality or injustice in the patient/caregiver. In a previous study among patients with intellectual disabilities and caregivers, all of the participants stressed the importance of developing information appropriate to each situation . The whole issue, in this context of difficult decisions, is how the health‐care teams and caregivers can accompany patients in their exercise of a form of autonomy – a relational autonomy – according to their needs, possibilities, and expectations.…”
Section: Discussionmentioning
confidence: 99%
“…The study was conducted between 01 June 2014 and 30 September 2015 at the Laboratory of Medical Ethics and Forensic Medicine of Paris Descartes University (France). The choice of method and the research questions were built from two previous studies in which patients and caregivers helped in an advisory capacity .…”
Section: Methodsmentioning
confidence: 99%